2014
DOI: 10.1039/c3cc47232a
|View full text |Cite
|
Sign up to set email alerts
|

Facile preparation of ammonium alginate-derived nanofibers carrying diverse therapeutic cargo

Abstract: Alginic acid was converted to a variety of ammonium alginate derivatives carrying diverse chemical cargo such as analgesics, antibiotics, and enzymes. These functional polymers could be fashioned into nanofibrous mats by electrostatic spinning. The therapeutic payload could be released in functional form by a simple ion exchange mechanism. Prospects in wound healing are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 31 publications
(2 reference statements)
0
19
0
Order By: Relevance
“…26 Recent literature has reported the carbon nanoparticles obtained from sodium alginate via ultrasonic-assisted nanoprecipitation and thermal acid dehydration, but the complicated synthesis processes, large nanoparticle sizes and low QYs without investigation at low pH values have limited their practical use. It has been in widespread use in water treatment, food additives, and biomedical materials.…”
Section: Synthetic Strategymentioning
confidence: 99%
“…26 Recent literature has reported the carbon nanoparticles obtained from sodium alginate via ultrasonic-assisted nanoprecipitation and thermal acid dehydration, but the complicated synthesis processes, large nanoparticle sizes and low QYs without investigation at low pH values have limited their practical use. It has been in widespread use in water treatment, food additives, and biomedical materials.…”
Section: Synthetic Strategymentioning
confidence: 99%
“…Similar studies reported that ionic interactions between bulk of carbohydrate polymers and small molecules improve drug affinity and long‐term release. In this regard, hyaluronic acid and alginate carriers have been applied. We showed that surface modification of PHEMA polymers using a highly charged polysaccharide like chitosan could improve ascorbic acid loading (most presumably though ionic interactions between opposite charges) and increase sustained release up to 10 days.…”
Section: Discussionmentioning
confidence: 99%
“…The usage of other natural polymers to form a polyelectrolyte complex toward biomedical applications has also been reported in the literature [48][49][50]. The polyelectrolyte complex made up of chitosan and alginate was prepared by employing a co-axial electrospinning technique [48].…”
Section: Advanced Electrospinning Techniquesmentioning
confidence: 99%